Higher Infliximab Trough Levels Are Associated With Better Outcome in Paediatric Patients With Inflammatory Bowel Disease. (19th September 2018) - van Hoeve, Karen; Dreesen, Erwin; Hoffman, Ilse; Van Assche, Gert; Ferrante, Marc; Gils, Ann; Vermeire, Séverine
Abstract: Background: The role of therapeutic drug monitoring for infliximab [IFX] therapy in children with inflammatory bowel disease [IBD] is poorly investigated. We determined if IFX exposure correlates with long-term remission in children. Methods: In this retrospective study, all children with Crohn's disease [CD] and ulcerative colitis [UC], receiving maintenance IFX at our centre, were included. Serum trough levels and cumulative drug exposure were correlated with clinical, biological, and endoscopic remission. All children received proactive drug monitoring and dose adaptation aiming to target a therapeutic window of 3–7 µg/mL. All data are presented as median [interquartile range]. Results: A total of 686 serum levels during IFX maintenance in 52 paediatric patients [33 CD and 19 UC] were included (median 9 [4–18] per patient). With a median of 17 [8–36] months under IFX therapy, 39/52 [75%] patients were in clinical remission and 29/40 [73%] patients were in endoscopic remission. Median IFX trough levels were significantly higher when children achieved clinical remission (5.4 [3.8–8.0] µg/mL versus 4.2 [2.6–6.7] µg/mL), biological remission (5.2 [3.7–7.7] µg/mL versus 4.2 [2.6–6.5] µg/mL), combined clinical and biological remission (5.7 [4.0–8.2] µg/mL versus 4.4 [2.7–6.8] µg/mL) and endoscopic remission (6.5 [4.2–9.5] µg/mL versus 3.2 [2.3–5.6] µg/mL) compared with not meeting these criteria [all p ≤ 0.001]. Conclusions: In this large paediatric cohort, children with clinical and/or endoscopic remission had significantly higher IFX exposure during maintenance therapy. We showed excellent outcome data using serial and systematic measurements of drug levels. This could provide a rationale for the use of proactive drug monitoring in children in order to improve long-term outcomes.